2020
DOI: 10.1111/eci.13346
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum soluble B7‐H4 in acute pancreatitis

Abstract: Background: Studies reported that soluble B7-H4 (sB7-H4) was significantly related to the progression and prognosis of inflammatory diseases, and whether sB7-H4 is related to the severity and prognosis of acute pancreatitis (AP) timely has not been reported. Materials and methods: Clinical database data of 446 AP patients were retrospectively collected, and the correlation between the expression serum levels of sB7-H4 with inflammatory factors and prognostic scores was analysed in AP patients. Results: Soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Cheng et al (2020) revealed that sB7-H4 could differentiate between health and AP, MAP and MSAP, and MSAP and SAP groups. The AUC for those groups were 0.958, 0.811, and 0.826, respectively, and the sensitivity and specificity could reach 86.5% and 96%, 81.8% and 67.9%, and 71.8% and 83.3%, respectively [18]. According to Chen et al (2017), sPD-L1 was an independent risk factor for infectious complications in AP, and the AUC of sPD-L1 for predicting infectious complications was 0.721, which were similar with lymphocyte count [19,20].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cheng et al (2020) revealed that sB7-H4 could differentiate between health and AP, MAP and MSAP, and MSAP and SAP groups. The AUC for those groups were 0.958, 0.811, and 0.826, respectively, and the sensitivity and specificity could reach 86.5% and 96%, 81.8% and 67.9%, and 71.8% and 83.3%, respectively [18]. According to Chen et al (2017), sPD-L1 was an independent risk factor for infectious complications in AP, and the AUC of sPD-L1 for predicting infectious complications was 0.721, which were similar with lymphocyte count [19,20].…”
Section: Discussionmentioning
confidence: 98%
“…Huang et al (2015) showed sB7-H2 could distinguish MSAP + SAP from MAP with 77.8% sensitivity and 80.0% specificity, whereas it distinguished SAP from MSAP + MAP with 92.0% sensitivity and 86.0% specificity [11]. Cheng et al (2020) revealed that sB7-H4 could differentiate between health and AP, MAP and MSAP, and MSAP and SAP groups. The AUC for those groups were 0.958, 0.811, and 0.826, respectively, and the sensitivity and specificity could reach 86.5% and 96%, 81.8% and 67.9%, and 71.8% and 83.3%, respectively [18].…”
Section: Discussionmentioning
confidence: 98%